2022
DOI: 10.4322/acr.2021.363
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-toxoplasmosis and fatal necrotizing cerebellitis

Abstract: Authors' contributions: Gabriele Gaggero was responsable for the macroscopic brain cutting and macro/ microscopic brain examination, and for conception, supervision and drafting of the article. Michela Campora was equally responsable for conception, supervision and drafting of the article. Beatrice Dose contributed to the macroscopic brain cutting, macroscopic brain examination and to the drafting of the article. Davide Taietti was responsible for the bibliography and image editing; he also contributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated the ability of T. gondii to induce cell death 67 69 . In order to investigate whether cell death accounts for the observed NPC and neuron loss in the T. gondii infected guinea pig neocortex, we analyzed cortical sections of the control and infection groups by immunohistochemistry using an antibody for caspase-3, a marker of programmed cell death (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated the ability of T. gondii to induce cell death 67 69 . In order to investigate whether cell death accounts for the observed NPC and neuron loss in the T. gondii infected guinea pig neocortex, we analyzed cortical sections of the control and infection groups by immunohistochemistry using an antibody for caspase-3, a marker of programmed cell death (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a therapeutic consideration: although there are very rare reports of fatal neurotoxoplasmosis [ 5 ], cerebral vasculitis is certainly more dangerous for the patient’s life, and the case described makes one reflect on the “strength” of ETs, trumping that of post-transplant immunosuppressive drugs, supporting the scientific community’s growing attention to potential pharmacological targets to control the formation or release of ETs [ 3 ].…”
mentioning
confidence: 99%
“…There are literature data correlating ETosis with inflammation, including vasculitis [2], or with parasitic infection [3], as well as some reports describing the association between neurotoxoplasmosis and cerebral vasculitis [4]. However, to the best of our knowledge, there are no data to date that microscopically document the continuum of neurotoxoplasmosis-ETosis-brain Finally, a therapeutic consideration: although there are very rare reports of fatal neurotoxoplasmosis [5], cerebral vasculitis is certainly more dangerous for the patient's life, and the case described makes one reflect on the "strength" of ETs, trumping that of post-transplant immunosuppressive drugs, supporting the scientific community's growing attention to potential pharmacological targets to control the formation or release of ETs [3].…”
mentioning
confidence: 99%